NFV em Redes 5G: Avaliando o Desempenho de Composição de Funções Virtualizadas via Maestro - Dalla-Costa, Ariel Galante; Schimuneck, Matias A. K.; Wickboldt, Juliano Araujo; Both, Cristiano Bonato; Gaspary, Luciano Paschoal; Granville, Lisandro Zambenedetti (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2017)
Dynamic Cloud Radio Access Network (Dynamic C-RAN) is an architecture wireless that aims benefits such as flexibility and agility to new five generation (5G) network. In Dynamic C-RAN, the radio functions processing is distributed along of a hierarchical of clouds. Network Functions Virtualization has been investigated the facilities to employ this wireless functions. NFV offers orchestration of split of radio functions into Virtualized Network Functions (VNF). The orchestrator needs to consider strict requirements of C-RAN between distributed components of VNF to get real earnings. In this work, we propose a detailed evaluation of Maestro - an NFV orchestrator for wireless environments aware VNF composition. We evaluate Maestro through of linear model programming, considering the effectiveness and orchestration overhead for deciding the best place to VNF components. In addition, we evaluate the trade-off between network data rate and time to generate the placement of components.